Pengaruh Coping Self Talk terhadap Keterasingan Siswa di SMA Negeri 2 Rantau Utara - Nurul Aini; Fadhilla Yusri (YASIN, 2026)
Social alienation among some Grade X Natural Sciences students at SMA Negeri 2 Rantau Utara was categorized as moderate, as indicated by their tendency to withdraw from social interactions, feel unaccepted by their environment, pay insufficient attention to personal hygiene, have low self-confidence regarding their physical appearance and hobbies, and experience difficulty participating in learning activities. This study aimed to analyze the effect of group counseling services using the self-talk technique on reducing students’ levels of social alienation. The study employed a quantitative approach using a pre-experimental method and a one-group pretest–posttest design. The research population comprised 93 Grade X Natural Sciences students, while the sample consisted of six students selected through purposive sampling. Data were collected using a social alienation questionnaire developed by the researcher and analyzed using the Wilcoxon signed-rank test with SPSS version 26. The results showed that the mean social alienation score decreased from 115.50 on the pretest, which was categorized as moderate, to 91.16 on the posttest, which was categorized as low. The hypothesis test yielded an Asymp. Sig. (2-tailed) value of 0.027 < 0.05, indicating a significant difference between the levels of social alienation before and after the intervention. Thus, group counseling services using the self-talk technique had a significant effect on reducing the level of social alienation among students at SMA Negeri 2 Rantau Utara. These findings provide practical implications for Guidance and Counseling teachers to use the self-talk technique in group counseling services to help students improve their self-acceptance, self-confidence, and social engagement.